Multivessel Spontaneous Coronary Artery Dissection in an Unlikely Patient - Waqas Jehangir; Tarek Aly; Kebir H. Bedran; Abdalla Yousif; Mark L. Niemiera (Case Reports in Cardiology)
When approaching the symptom of acute onset chest pain in a previously healthy 26-year-old male, anchoring heuristic presents a challenge to healthcare workers. This diagnostic error is the healthcare professional’s tendency to rely on a previous diagnosis, and, in situations where a set of symptoms might mask a rare and deadly condition, this error can prove fatal for the patient. One such condition, Spontaneous Coronary Artery Dissection (SCAD), is an uncommon and malefic presentation of coronary artery disease that can lead to myocardial infarction and sudden death. We present a case of SCAD in an otherwise healthy 26 year-old male who had been experiencing chest pain during and after sports activity. In the young, athletic male with SCAD, the danger of diagnostic error was a reality due to the broad symptomatology and the betraying demographics.